2002
DOI: 10.1128/iai.70.4.2065-2069.2002
|View full text |Cite
|
Sign up to set email alerts
|

Stachylysin May Be a Cause of Hemorrhaging in Humans Exposed to Stachybotrys chartarum

Abstract: Stachybotrys chartarum is a toxigenic fungus that has been associated with human health concerns such as nasal bleeding in adults and pulmonary hemosiderosis (PH) in infants. Seven of eight strains of S. chartarum isolated from homes of infants with PH in Cleveland, Ohio, and the strain from the lung of an infant with PH in Texas produced stachylysin in tryptic soy broth (TSB), whereas only one out of eight strains isolated from control homes produced stachylysin. However, all strains produced stachylysin when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…A series of articles linking environmental exposure to fungi (especially Stachybotrys atra) in water-damaged houses in Cleveland, OH, USA and infantile pulmonary haemosiderosis led to an extensive investigation of possible infectious or mycotoxigenic pathogenesis [46][47][48][49][50][51][52][53][54][55][56][57][58]. The postulated mechanism is that fungal toxins called trichotecens, which are potent protein synthesis inhibitors, impede the angiogenesis underneath the rapidly forming alveolar membranes, making the acinar region prone to bleeding.…”
Section: Environmental Theorymentioning
confidence: 99%
“…A series of articles linking environmental exposure to fungi (especially Stachybotrys atra) in water-damaged houses in Cleveland, OH, USA and infantile pulmonary haemosiderosis led to an extensive investigation of possible infectious or mycotoxigenic pathogenesis [46][47][48][49][50][51][52][53][54][55][56][57][58]. The postulated mechanism is that fungal toxins called trichotecens, which are potent protein synthesis inhibitors, impede the angiogenesis underneath the rapidly forming alveolar membranes, making the acinar region prone to bleeding.…”
Section: Environmental Theorymentioning
confidence: 99%
“…Stachylysin injected into the earthworm Lumbricus terrestis resulted in the leakage of hemoglobin from the animal's vascular system (Vesper and Vesper, 2002). We showed that stachylysin caused pores in sheep 200 VESPER AND VESPER RBC membranes (Vesper et al, 2001), but L. terrestis has no oxygencarrying cells and a closed vascular system.…”
Section: Stachylysinmentioning
confidence: 89%
“…Exposure to S. chartarum has been shown to cause hemorrhaging in animals (Forgacs, 1972;Sarkisov and Orshanskaiya, 1944) and agricultural workers (Hintikka, 1978;Rylander,1994;Sorenson and Lewis, 1996). The hemolysin stachylysin caused hemorrhaging in an animal model (Vesper and Vesper, 2002). Thus there are a number of cases where fungal hemolysins cause damage to or destruction of vascular tissues.…”
Section: Symptoms Associated With Vascular Tissue Damagementioning
confidence: 99%
See 1 more Smart Citation
“…2,3 After incubation, the coated plates w ere washed three times with phosphate-buffered saline-0.05% Tween 20 (PBST, Sigma). Standards of 11 different concentrations of stachy lysin-BSA (0 to 62.5 ng/ml) diluted in 1: 20 diluted (PBST) commercially available human sera o r diluted (1:20 in PBS T) subject sera (in triplicate) were mixed with affinit y-purified rabbit antistachylysin IgG ( Bethyl Larboratories, Montgomery, TX) diluted 1:20,000 in PBST) in test tubes and incubated at 4°C for 2 4 hours.…”
Section: Stachylysin™ Assaymentioning
confidence: 99%